Application of Exosomes-Derived Mesenchymal Stem Cells in Treatment of Fungal Diseases: From Basic to Clinical Sciences - Ghasemian, Seyedeh Ommolbanin (Frontiers in Fungal Biology, 2021)
Fungal diseases such as candidiasis are some of the deadliest diseases among immunocompromised patients. These fungi naturally exist on human skin and throughout the digestive system. When the microbiota balance becomes upset, these fungi become pathogenic and potentially lethal. At the pathogenesis of fungal diseases, host immune system response is diverse. At the early stages of fungal pathogenesis such as Candida albicans, it was shown that these fungi use the immune cells of the host body and cause malfunction the early induction of proinflammatory cytokines of the host body leading to a reduction in their numbers. However, at some stages of fungal diseases, the immune response is severe. Despite many treatments already being available, it seems that one of the best treatments could be an immune-stimulatory agent. Some of the subsets of MSCs and exosome-derived cells, as a cell-to-cell communicator agent, have many roles in the human body, including anti-inflammatory and immune-modulatory effects. However, the TLR4-primed and IL-17+ subsets of MSCs have been shown to have immune-stimulatory effects. These subsets of the MSCs produce pro-inflammatory cytokines and reduce immunosuppressive cytokines and chemokines. Thus, they could trigger inflammation and stop fungal pathogenesis. As some biological activities and molecules inherit elements of their exosomes from their maternal cells, the exosome-derived TLR4-primed and IL-17+ subsets of MSCs could be a good candidate for fighting against fungal diseases. The applications of exosomes in human diseases are well-known and expanding. It is time to investigate the exosomes application in fungal diseases. In this review, the probable role of exosomes in treating fungal diseases is explored.